Informe de resultados de la encuesta CIEP-UCR - Alfaro Redondo, Ronald; Guzmán Castillo, Jesús 1989-; Chacón Mendoza, Daniela; Camacho Sánchez, Sharon Mariela 1995-; Gamboa Sanabria, César; Chinchilla Zorilla, Vianca; Ruiz Tijerino, María de Fátima 1994-; Contreras Ibarra, Andrés (Centro de Investigacion y Estudios Politicos, 2021)
Este informe publicado el 01 de setiembre de 2021